The Implementation of Paper Mobile Phone Media on Describing People Physical Appearance to Enhance Students’ Speaking Skill - Yuwono, Farah Amaliyah; Santoso, Dian Rahma (PROJECT (Professional Journal of English Education), 2025)
This study discussed the implementation of using Paper Mobile Phone Media to enhance English speaking skills for 8 grade students at SMPN 1 Wonoayu, Sidoarjo. To engage the key challenges such as lack of parental motivation, difficulties in pronunciation, and limited vocabulary retention, this research employed a pre-experimental design with pre- and post- tests. The results indicated significant improvements in students' speaking abilities, particularly in pronunciation and vocabulary usage, following two targeted treatments focused on descriptive text related to physical appearance. The ending results showed that there was significant difference between pre- and post- tests. The median score for the pre-test was more than half of students’ amount who got the minimum of total score, but if looked from scores of aspects assessment in this pre-test still much students who got scores below the maximum of aspects assessments’ score. Meanwhile, the median score for the post-test was surely more than half of students’ amount who got the targets minimum of total score, it can looked from scores of aspects assessment in this post-test had many students also got scores better than pre-test before.